Thermal deformation generated on a CFRP laminated reflector - Shun TANAKA (The Japan Society of Mechanical Engineers, 2016)
Carbon Fiber Reinforced Plastic (CFRP) has high specific stiffness and its thermal deformation can be controlled by fiber orientation. Therefore, it is often adopted as a material of space observation systems. In this study, experiment, numerical and analytical calculation on thermal deformation of CFRP reflector models were conducted to investigate the characteristics of thermal deformation of CFRP reflectors (mirrors) for space observation systems. Two types of reflector models were manufactured, which were comprised of a quasi-isotropic CFRP laminate with and without an sprayed aluminum layer and a polyurethane layer on the top surface. The experimental results showed that the out-of-plane thermal deformation of the reflector model with the aluminum and polyurethane layers is considerably larger than that of the reflector model without the aluminum and polyurethane layers and maximum and minimum displacement were observed in specific directions. The result of the numerical calculation showed the same trend. Additionally, this trend was discussed analytically. Moreover, uncertainty of the structure and method of reducing out-of-plane displacement were discussed. When shape control to suppress thermal deformation of CFRP reflectors is considered, the result obtained in this work is important to determine the optimal placement of actuators.